2006
DOI: 10.1159/000089183
|View full text |Cite
|
Sign up to set email alerts
|

Relative Medial and Dorsal Cortex Volume in Relation to Sex Differences in Spatial Ecology of a Snake Population

Abstract: In non-avian reptiles the medial and dorsal cortices are putative homologues of the hippocampal formation in mammals and birds. Studies on mammals and birds commonly report neuro-ecological correlations between hippocampal volume and aspects of spatial ecology. We examined the relationship between putative homologous cortical volumes and spatial use in a population of the squamate reptile, Agkistrodon piscivorus, that exhibits sex differences in spatial use. Do male A. piscivorus that inhabit larger home range… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
44
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(49 citation statements)
references
References 138 publications
4
44
1
Order By: Relevance
“…Thus, the MC in Acanthodactylus boskianus, an active forager, is larger than in A. scutellatus, a sit-and-wait predator [41] [42]. In the snake Agkistrodon piscivorus, males, that have larger home ranges than females, present a larger MC as well as increased neurogenesis and cell migration relative to the dorsal cortex [43]. Territorial males of side-blotched lizards (Uta stansburiana) that inhabit broader areas have increased MC neurogenesis rate when compared with those living in smaller (spatially impoverished) areas [44].…”
Section: Medial Pallium or Hippocampus And Map-like Memories In Amniotesmentioning
confidence: 98%
“…Thus, the MC in Acanthodactylus boskianus, an active forager, is larger than in A. scutellatus, a sit-and-wait predator [41] [42]. In the snake Agkistrodon piscivorus, males, that have larger home ranges than females, present a larger MC as well as increased neurogenesis and cell migration relative to the dorsal cortex [43]. Territorial males of side-blotched lizards (Uta stansburiana) that inhabit broader areas have increased MC neurogenesis rate when compared with those living in smaller (spatially impoverished) areas [44].…”
Section: Medial Pallium or Hippocampus And Map-like Memories In Amniotesmentioning
confidence: 98%
“…Since both climbing trees and burrowing underground in 3-dimensions is part of the behavioral repertoire of P. regius, they too may require a MC system that allows for two interconnected but structurally and functionally different MC systems (Hoogland and Vermeulen-Vanderzee, 1995). Regional variation in the MC of snakes is further supported by Roth et al (2006), who found sex differences in cortex volume relative to telencephalon volume only in the caudal half of the medial cortex.…”
Section: Rostral-caudal Effectsmentioning
confidence: 97%
“…Also, lesioning the medial and dorsal cortices of turtles causes a reduction in maze navigation ability (Lopez et al, 2003;Rodriguez et al, 2002) and produces deficits in a variety of non-spatial tasks such as discrimination and restraint habituation (Blau and Powers, 1989;Grisham and Powers, 1989;Moran et al, 1998). In squamate reptiles including snakes, the MC is also associated with navigation ability (Baird Day et al, 1999a;Baird Day et al, 1999b;Crews and Wilczynski, 2000;Holding et al, 2012;LaDage et al, 2009;Roth et al, 2006).…”
Section: The Dorsal and Medial Cortexmentioning
confidence: 99%
“…This increase in volume of these brain regions, or the hippocampus in mammals and birds, is mediated, at least in part, through increases in neurogenesis (Rats: Drapeau et al, 2003;Roof and Havens, 1992;Birds: LaDage et al, 2010). In reptiles, the medial and dorsal cortices (MC and DC, respectively) are considered hippocampal homologues and similarly display plasticity with regards to spatial ecology and territory or home range size (Holding et al, 2012;LaDage et al, 2009;Roth et al, 2006. Male cottonmouth snakes (Agkistrodon piscivorus) have larger MC compared to female conspecifics (Roth et al, 2006), presumably due to a sexual dimorphism in spatial movements.…”
Section: Introductionmentioning
confidence: 99%
“…In reptiles, the medial and dorsal cortices (MC and DC, respectively) are considered hippocampal homologues and similarly display plasticity with regards to spatial ecology and territory or home range size (Holding et al, 2012;LaDage et al, 2009;Roth et al, 2006. Male cottonmouth snakes (Agkistrodon piscivorus) have larger MC compared to female conspecifics (Roth et al, 2006), presumably due to a sexual dimorphism in spatial movements. In male Northern Pacific rattlesnakes (Crotalus oreganus), short distance translocations caused increased home range size and an increase in MC volume (Holding et al, 2012 (Brown et al, 2003).…”
Section: Introductionmentioning
confidence: 99%